Ultrastable heterodyne interferometry using a modulated light camera - Patel, Rikesh Ramesh (2014)
Interferometry is used in a wide variety of fields for the instrumentation and analysis of subjects and the environment. When light beams interfere, an interference fringe pattern is generated. Captured widefield interference patterns can be used to determine changes in the optical path length of interfering beams across a 2D area. Two interferometer schemes regularly implemented in modern systems include the homodyne interferometer, where light with the same optical frequency in used to generate static intensity fringe patterns, and the heterodyne interferometer, where light with different optical frequencies are used to generate a fringe pattern that is modulated at a frequency equal to the optical frequency difference (beat frequency). A widefield heterodyne system is not straightforward to bring into practice, however, it does offer some benefits over a comparable homodyne interferometer, such as direct phase interpretation and the suppression of low frequency background light in interferograms.